A quality of experience evaluation method for an UAV first person view system - González, Nuria; Solera-Delgado, Marta; Ruiz-Vega, Fernando Jesús; Luna-Ramírez, Salvador; Toril-Genovés, Matías (My University, 2022)
Unmanned Aerial Vehicles (UAV) communication systems are an increasingly widespread and emerging technology due to their flexibility, low cost and usability properties. Hence, the demand for Beyond Visual Line of Sight (BVLOS) cases that require large data transmission and low latency in cellular networks are increasingly. In this work, the assembly, integration and networking of a UAV quadrotor for First Person View (FPV) system connected by LTE is presented. Different configurations of the link between the UAV and the Ground Control Station (GCS) are proposed, such as connection by LTE cloud-based server, direct LTE connection and direct WiFi connection. With these configurations, experiments are carried out to characterise the network metrics that model this service according to the telemetry, control and video traffic. The main contribution is the definition of a closed mathematical expression provided to define the Quality of Experience (QoE) for FPV use cases considering the video quality in terms of Video Multimethod Assessment Fusion (VMAF), network latency and video resolution as inputs. This expression will be applied to lab experiments taking into account link performance, in which network changes based in packet loss and latency alterations will be introduced to measure the QoE of the UAV system.
Keywords: Vehículos autodirigidos; Aviones sin piloto; Sistemas de comunicaciones inalámbricos; Quality of Experience; Unmanned Aerial Vehicle; First Person View; Beyond Visual Line of Sight; Ground Control Station; Video Multimethod Assessment Fusion; latency; packet loss; LTE